Inhalable dry powder nano-formulations: advancing lung disease therapy-a review - Naureen, Faiza; Shah, Yasar; Rehman, Maqsood ur; Chaubey, Pramila; Nair, Anjana Karunakaran; Khan, Jahangir; Abdullah,; Shafique, Muhammad; Shah, Kifayat Ullah; Ahmad, Bashir (Frontiers in Nanotechnology, 2024)
Human exposure to various respiratory diseases has sparked an interest among scientists to propose and promote inhalable nanoparticle-based products.This new drug delivery system will be an effective and prompt therapy for next-generation respiratory therapeutics.There are many formulations to treat lung diseases,i.e.,oral, injectable, aerosol, nebulizer-based, etc. But,due to extended distribution and elimination, repeated intake, and complex systems of application,these treatments create overload on patients along with other expenses of daily life.Amid these treatments, inhalable nanoparticlebased dry powder formulations are considered superior owing to their simplicity,convenience of use,and long-term stability.This review aims to formulate an inhalable nanoparticle dry powder formulation to attain confined distribution of the remedy to the respiratory system.Dry powder formulations based on inhalable nanoparticles provide a novel and cutting-edge method of treating lung conditions.This novel drug delivery system is an improved treatment for lung disorders in terms of its efficacy and reduced dose requirement. Subsequently,the availability of this formulation will be an alternative option for patients to improve treatment compliance and,foremost, therapeutic outcomes in different lung ailments.The salient features of dry formulations that illustrate their uniqueness are deep penetration to lung tissues, enhanced deposition in lung regions, improved solubility, elevated bioavailability, targeted drug delivery, stability at storage, convenient to use,versatile and customizable formulation.This novel inhalable formulation is based on finely dried nanoparticles or freeze-dried particles. This formulation will contain an excessive amount of dried nanoparticles, and if it is combined with a beneficial tool, i.e.,a spray/pump/puffer, it will be a pleasant way to apply drugs directly to the lungs.